An extensive electrostatic analysis of dual material gate all around tunnel FET (DMGAA-TFET). (24th May 2016) - Dash, S; Mishra, G P
Abstract: In the proposed work an analytical model of a p-channel dual material gate all around tunnel FET (DMGAA-TFET) is presented and its performance is compared with the conventional GAA-TFET. The electrostatic potential profile of the model is obtained using 2-D Laplace's solution in the cylindrical coordinate system. A quantitative study of the drain current has been carried out using electric field in the z -axis and tunneling path. However the potential and current analysis is prolonged to different combinations of gate length in the DMGAA-TFET model. The results show an improvement in drain current and subthreshold swing as compared to GAA-TFET, which makes this model a potential replacement for low power application. Also the effect of scaling of the gate oxide thickness and cylindrical pillar diameter on the surface potential, initial tunneling point and tunneling current are analyzed.